Hot clothes burn those who report: Proposals based on decolonial feminism for overcoming gender violence at public universities - Lisboa, Natália; Pereira, Flávia (Comparative Cultural Studies: European and Latin American Perspectives, 2024)
It begins with the problem of how to confront gender coloniality as manifested in violence against women at the university through three questions based on the theoretical framework of decolonial feminism: where do we come from? - seeking to identify our social and epistemic location; where do we find ourselves? - The possibilities of decolonial feminism as a theory of practice, represented by projects against gender violence at the Federal University of Ouro Preto, such as the Office of the Dean of Student Community Affairs (Prace) and the Women’s Ombudsman; and where are we going? - Recognising the limits and challenges of everyday practice, without deviating from the necessary self-criticism based on decolonial feminism. In order to achieve these objectives, the concept of a public university is used in a broad sense, encompassing the quadriplegic of teaching-research-extension-student support and the administrative activities carried out by students and staff, recognising its plural role in social transformation based on overcoming epistemic, structural and institutional violence.